Abandonment of natural gas production and investment in carbon storage. (September 2017) - Hauck, Dominic; Hof, Andries F.
Abstract: Long-term mitigation scenarios rely heavily on Carbon Capture and Storage (CCS) for achieving ambitious climate change targets. The amount of CO2 storage in these scenarios depends on the CO2 price and exogenously determined availability and costs of storage capacity. We analyze investment in CCS in more detail by taking the opportunity costs of CO2 storage into account, assuming that CO2 injection and resource extraction are mutually exclusive. Using real option valuation, we study the impact of i) correlation between gas and CO2 prices, ii) volatility of CO2 prices, and iii) regulatory deadlines on the value of the option to invest in CCS. We find that the value of the option to exchange gas production for CO2 injection is decreasing in the correlation of gas and CO2 prices, but increasing in the volatility of CO2 prices, and in shorter regulatory deadlines for removal of gas production facilities. This implies that next to consistent and high pricing of CO2, extending the deadline for removal of gas production facilities could increase the incentive to invest in CO2 storage in mature gas fields. We argue that considering these dynamics in mitigation scenarios could lead to more realistic projections of CCS application. Highlights: The option value for CCS investment depends on decision to abandon gas production. We evaluate abandonment of gas fields and investment in CCS by real option analysis. Positively correlated gas and CO2 prices negatively affects the option value of CCS. Postponing abandonment cost of gas fields has little impact on the CCS option value. If gas production facilities need to be removed fast, the CCS option value is lower.